2017
DOI: 10.1186/s40249-017-0284-4
|View full text |Cite
|
Sign up to set email alerts
|

The strategic framework of tuberculosis control and prevention in the elderly: a scoping review towards End TB targets

Abstract: With the rapid pace of population ageing, tuberculosis (TB) in the elderly increasingly becomes a public health challenge. Despite the increasing burden and high risks for TB in the elderly, targeted strategy has not been well understood and evaluated. We undertook a scoping review to identify current TB strategies, research and policy gaps in the elderly and summarized the results within a strategic framework towards End TB targets. Databases of Embase, MEDLINE, Global health and EBM reviews were searched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 53 publications
(264 reference statements)
2
39
0
Order By: Relevance
“…Together, this suggests that the current emphasis on HIV and TB co-morbidity is not sufficient to address the challenges of this under-diagnosed pool of older HIV-uninfected older adults who may have particular challenges with regard to health access due to poverty, rural living, mobility difficulties [ 32 ] and ageist stigma [ 33 ]. There is currently limited evidence regarding successful interventions for the improvement of diagnosis of TB among older adults in LMICs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, this suggests that the current emphasis on HIV and TB co-morbidity is not sufficient to address the challenges of this under-diagnosed pool of older HIV-uninfected older adults who may have particular challenges with regard to health access due to poverty, rural living, mobility difficulties [ 32 ] and ageist stigma [ 33 ]. There is currently limited evidence regarding successful interventions for the improvement of diagnosis of TB among older adults in LMICs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively high rates of TB among older adults challenge the current TB response and require new data and thinking. Li and colleagues’ recent scoping review [ 34 ] identified a number of causal pathways to improve TB prevention and services among older people. While the review focused on articles from high-income countries [ 34 ], some of the interventions might be relevant in low- and middle-income settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the increase in respiratory pathology associated with increase in age including pneumonia, chronic obstructive pulmonary disease among others. (22) Therefore, the CXR is not a preferred TB screening test among these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, no age-related differences were found in the Northern California registry [119]. Thus, the role of ageing as additional risk factors for TB [120] in patients under biological treatment needs to be further investigated.…”
Section: Comorbidities and Increased Risk Of Tb Reactivationmentioning
confidence: 95%